Green tea and its active compound epigallocathechin-3-gallate (EGCG) inhibit neuronal apoptosis in a middle cerebral artery occlusion (MCAO) model - Abdulloh Machin, Abdulloh
Abstract Objectives: To determine the effect of green tea with the active ingredient epigallocathechin-3-gallate (EGCG) on the inhibition of apoptosis in the middle cerebral artery occlusion (MCAO) model.